Preparation method for constructing organic-inorganic hybrid structure on surface of carbon fiber, product and application

By constructing an organic-inorganic hybrid structure of metal polyphenol network and carbon nanotubes on the surface of carbon fiber, the problem of insufficient interface performance of carbon fiber composite materials is solved, and high-strength and tough composite materials are prepared, with simple process and low cost.

CN119859916AActive Publication Date: 2025-04-22UNIV OF JINAN
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510055209.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-06
Filing Date
2025-01-14
Publication Date
2025-04-22
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

In practical applications, carbon fiber composite materials are prone to damage such as interface debonding and matrix fracture, which affects their impact strength, structural toughness and service life. The existing technology lacks an orderly self-assembly method using metal polyphenol networks and carbon nanotubes to improve the interface performance of the carbon fiber surface.

Method used

By constructing an organic-inorganic hybrid structure of metal polyphenol network and carbon nanotubes on the surface of carbon fibers, it can achieve rapid and orderly self-assembly by using ultrasonic impregnation and rinsing steps to form oxygen-containing functional groups that can react with the polymer matrix, thereby improving interface interactions.

Benefits of technology

The interlayer shear strength and bending strength of carbon fiber reinforced epoxy resin composites are significantly improved, their comprehensive performance is improved, and the preparation cost and time are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859916A_ABST
    Figure CN119859916A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of carbon fiber interface modification, in particular to a preparation method for constructing an organic-inorganic hybrid structure on the surface of carbon fiber, a product and application. The preparation method comprises the following steps: performing desizing treatment on carbon fibers in acetone to obtain desized carbon fibers; respectively preparing an MPN solution and a CNTs turbid liquid; the desized carbon fibers are soaked in an MPN solution and a CNTs turbid liquid respectively for ultrasonic oscillation and then dried, and a metal polyphenol network and carbon nanotube coated carbon fibers are obtained; and uniformly mixing the MPN solution and the CNTs turbid liquid, soaking the desized carbon fiber in the MPN and CNTs mixed solution, carrying out ultrasonic oscillation, and drying to obtain the metal polyphenol network and carbon nanotube coated carbon fiber. The surface of the carbon fiber is coated with the carbon nano tube and the metal polyphenol network, the advantages of the carbon nano tube and the metal polyphenol network are utilized, an organic-inorganic hybrid structure is constructed on the surface of the carbon fiber, and the product performance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of carbon fiber interface modification, in particular to a preparation method, product and application of an organic-inorganic hybrid structure constructed by using the surface of carbon fiber. Background Art

[0002] Carbon fiber reinforced resin-based composites (CFRP) have excellent properties such as high specific strength, high specific modulus, fatigue resistance, corrosion resistance, designability, and structural molding integration, and have been widely used in the aerospace industry. However, due to the influence of the production process, the surface of carbon fiber is smooth and chemically inert. After being compounded with resin, the interface area is prone to damage such as interface debonding and matrix fracture, which greatly affects the impact strength, structural toughness and service life of CFRP. Therefore, in order to meet the strength requirements of carbon fiber composites in practical applications, the surface of carbon fiber must be modified, usually by physical or chemical effects to improve the surface roughness and polar functional groups of carbon fiber and improve the wettability of resin matrix to fiber surface. The interface performance of composite materials is enhanced by introducing chemical bonding and mechanical meshing in the interface phase.

[0003] Polyphenols have abundant functional groups, such as catechol and galloyl, which can interact with other molecules in various ways. Carbon nanotubes (CNTs) are a special one-dimensional quantum material, which is a concentric tube composed of hexagonally arranged carbon atoms with a diameter of up to dozens of layers at the nanoscale. They have potential applications in the surface modification of carbon fibers.

[0004] In the prior art, there is a lack of reports on the modification methods of carbon fibers that utilize the strong adhesion of metal polyphenol networks and the strong π-π conjugation of carbon nanotubes to quickly and orderly self-assemble an "organic-inorganic" hybrid structure on the surface of carbon fibers, and there are few studies on the application of metal polyphenol networks and carbon nanotube-coated carbon fibers in composite materials. Therefore, there is an urgent need for a preparation method that is simple in production process, low in cost, and utilizes the surface of carbon fibers to construct an organic-inorganic hybrid structure. Summary of the invention

[0005] The present invention aims to solve the above problems and provides a preparation method, product and application of an organic-inorganic hybrid structure constructed on the surface of carbon fiber. The preparation process is simple, the cost is low, it is green and environmentally friendly, and the product performance is excellent.

[0006] The first object of the present invention is to provide a preparation method for constructing an organic-inorganic hybrid structure using the surface of carbon fiber, the preparation method comprising the following steps:

[0007] Step 1: Desizing the carbon fiber in acetone to obtain desizing carbon fiber; the amount of acetone used is sufficient to ensure the desizing of the carbon fiber, such as 1-5 times the mass of the carbon fiber. Step 2: Dissolve tannic acid and FeCl3·6H2O in deionized water, stir and mix to obtain a metal polyphenol network solution, i.e., MPN solution; the molar ratio of tannic acid to FeCl3·6H2O is 1:1-3;

[0008] Step 3: dissolving carbon nanotubes in deionized water and ultrasonically obtaining a carbon nanotube suspension, i.e., a CNTs suspension;

[0009] Step 4: firstly place the desized carbon fiber in the MPN solution for ultrasonic immersion, then rinse and then place the MPN-coated carbon fiber in the CNTs suspension for ultrasonic immersion, rinse again, repeat the above operation until the supernatant is colorless and transparent, and then dry to obtain the metal polyphenol network and carbon nanotube-coated carbon fiber;

[0010] The mass ratio of tannic acid to carbon nanotubes is 4.25:0.05-0.15.

[0011] This solution is further improved. In step 1, the acetone desizing temperature is 60° C. to 80° C., and the desizing time is 36 to 72 hours.

[0012] This solution is further improved. In step 2, the mass volume ratio (g:ml) of tannic acid and deionized water is 4.25:200; the mixture is stirred and mixed with a magnetic stirrer for 5-15 minutes at a stirring rate of 900-1200 r / min; the tannic acid and Fe in the obtained MPN solution are 3+ The molar ratio is 1:1~3.

[0013] This solution is further improved, in step 3, the ultrasonic frequency is 80 to 120 kHz, more preferably 90 to 110 kHz; more preferably 100 kHz; the ultrasonic time is 5 to 30 minutes.

[0014] This scheme is further improved, the ultrasonic frequency in step 4 is 80-120kHz, more preferably 90-110kHz; more preferably 100kHz; ultrasonic immersion is 5-20min min, the drying temperature is 50-70°C; the drying time is 5-7h; the number of immersion cycles is 1-3 times, preferably 1 time, and the number of cleanings is preferably 3-5 times.

[0015] This solution is further improved, in which the mass ratio of the MPN solution to the CNTs suspension in step 4 is 1-2:1-2, preferably 1:1; the mass ratio of the desized carbon fiber to the tannic acid in step 2 is 10:4.25.

[0016] This solution can be further improved to include the following steps:

[0017] Step 1: Put the carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48 hours, take it out after the reaction is completed, wash it with deionized water 5 times, and dry it to obtain desized carbon fiber;

[0018] Step 2: Dissolve 4.25 g tannic acid and 2.03 g FeCl3·6H2O powder in 200 ml deionized water and stir with a magnetic stirrer for 10 min at a stirring rate of 1000 r / min to obtain TA and Fe 3+ Metal polyphenol network solution with a molar ratio of 1:3;

[0019] Step 3: Dissolve 0.1 g of carbon nanotubes in 200 ml of deionized water and ultrasonicate at 100 kHz for 30 min to obtain a carbon nanotube suspension;

[0020] Step 4: Place 10g of desized carbon fiber in the MPN solution for ultrasonic immersion for 10 minutes, then rinse with deionized water for 3 times, then place the MPN-coated carbon fiber in the CNTs suspension for ultrasonic immersion for 10 minutes, rinse with deionized water again for 3 times until the supernatant is colorless and transparent, and then place it in a drying oven at 60°C for 6 hours to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

[0021] In a second aspect, the present invention provides a metal polyphenol network and carbon nanotube-coated carbon fiber obtained by the above method.

[0022] In a third aspect, the present invention provides an application of a metal polyphenol network and carbon nanotube coated carbon fibers in a composite material. The metal polyphenol network and carbon nanotube coated carbon fibers are compounded with epoxy resin and the composite material is prepared by a molding process.

[0023] This scheme is further improved, the metal polyphenol network and the carbon nanotube coated carbon fiber account for 63% of the volume fraction of the composite material; the metal polyphenol network and the carbon nanotube coated carbon fiber are fully impregnated in the epoxy resin E51, the temperature of the vulcanizer is adjusted to 90°C, the mold wrapped with the metal polyphenol network and the carbon nanotube coated carbon fiber impregnated with the resin is placed in the vulcanizer for preheating, and then the pressure is adjusted to 5MPa through the pressure control system, the molding system is started, and maintained at 90°C and 5MPa for 1h; then the temperature is adjusted to 120°C and the pressure is 10MPa, and maintained for 2h; finally, the temperature is adjusted to 150°C and the pressure is 10MPa, and maintained for 3h; after the molding is completed, it is naturally cooled to room temperature under the pressure holding state, and demolded to obtain a composite material.

[0024] The beneficial effects of the present invention are:

[0025] (1) The present invention provides a preparation method for constructing an organic-inorganic hybrid structure on the surface of carbon fiber. The preparation method is simple in process, environmentally friendly, low in cost, and effectively shortens the preparation time, and is suitable for promotion and application.

[0026] (2) Since carbon nanotubes are tubular, when they are dispersed in the coating, they easily form a dense network structure and reduce the holes in the coating. Therefore, using carbon nanotubes to modify carbon fibers increases the surface roughness of the fibers, which can effectively improve their mechanical properties and enhance the interfacial bonding force between them and the matrix, thereby improving their overall performance. In addition, carbon nanotubes (CNTs) can be embedded in the resin matrix to increase the mechanical meshing between the fibers and the resin matrix.

[0027] Tannic acid (TA) is a kind of natural compound polyphenol. The pyrogallol hydroxyl group in the molecular structure has high affinity, and the coupling groups in tannic acid (TA) interact through hydrogen bonds or π-π bonds to form oligomers. Tannic acid (TA) and Fe 3+ The metal polyphenol network (MPN) material formed by complexation has the characteristics of large pore size and specific surface area, so Fe 3+ and tannic acid (TA) can be assembled on substrate surfaces of different shapes and sizes to obtain a two-dimensional or three-dimensional metal polyphenol network structure to improve its performance. The present invention coats the carbon fiber surface with carbon nanotubes and metal polyphenol networks, utilizes the advantages of both parties, exerts a synergistic effect, realizes the construction of an organic-inorganic hybrid structure on the carbon fiber surface, and improves product performance.

[0028] (3) The present invention provides a preparation method for constructing an organic-inorganic hybrid structure using the surface of carbon fiber, in which a metal polyphenol network and carbon fiber are coated on the surface of the carbon fiber, and the strong adhesion of the metal polyphenol network and the π-π conjugation of carbon nanotubes are used to quickly and orderly self-assemble the "organic-inorganic" hybrid structure on the surface of the carbon fiber to form oxygen-containing functional groups that can react with the polymer matrix, thereby achieving the strong interfacial interaction required in carbon fiber reinforced epoxy resin (composite material), and can significantly improve the interlaminar shear strength and bending strength of the metal polyphenol network and carbon nanotube-coated carbon fiber reinforced epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a morphology diagram of the desized carbon fiber obtained in Example 1;

[0030] Figure 2 The morphology of the metal polyphenol network and carbon nanotube-coated carbon fiber obtained in Example 1;

[0031] Figure 3 This is a scanning electron microscope image of the fracture surface of the desized carbon fiber reinforced composite material obtained in Example 2;

[0032] Figure 4 This is a scanning electron microscope image of the fracture surface of the metal polyphenol network and carbon nanotube-coated carbon fiber reinforced composite material obtained in Example 2. DETAILED DESCRIPTION

[0033] In order to better understand the present invention, the technical solution of the present invention is described in detail with specific examples below, but the present invention is not limited thereto.

[0034] Other raw materials used in the present invention are all commercially available products.

[0035] Example 1

[0036] The carbon fiber was placed in a Soxhlet extractor, acetone was added, the temperature was raised to 68°C, and the reaction was carried out for 48 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0037] 4.25 g of tannic acid and 2.03 g of FeCl3·6H2O powder were dissolved in 200 ml of deionized water and stirred with a magnetic stirrer for 10 min (stirring and mixing at a rate of 1000 r / min) to obtain TA and Fe 3+ Metal polyphenol network (MPN) solution with a molar ratio of 1:3;

[0038] 0.1 g of carbon nanotubes was dissolved in 200 ml of deionized water and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension;

[0039] 10 g of desized carbon fiber was first placed in an MPN solution for ultrasonic immersion for 10 min (the frequency of ultrasonic oscillation was 100 kHz), then rinsed with deionized water for 3 times, and then the desized carbon fiber was placed in a CNTs suspension for ultrasonic immersion for 10 min (the frequency of ultrasonic oscillation was 100 kHz), and then rinsed with deionized water for 3 times until the supernatant was colorless and transparent, and then the carbon fiber was placed in an electric blast drying oven and dried at 60°C for 6 h to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

[0040] The morphology of the desized carbon fiber obtained in Example 1 is as follows: Figure 1 The morphology of metal polyphenol network and carbon nanotube coated carbon fiber is shown in Figure 2 shown.

[0041] The desizing carbon fiber, MPN and CNTs coated carbon fiber obtained in Example 1 were respectively compounded with epoxy resin E51, and a composite material (desizing carbon fiber, MPN and CNTs coated carbon fiber were 63% of the composite material volume fraction) was prepared by a flat vulcanizer through a molding process, and the interlaminar shear strength (ILSS) and bending strength of the composite material were tested. The method for preparing the composite material is: the desizing carbon fiber and the MPN and CNTs coated carbon fiber are fully impregnated in epoxy resin E51, respectively, to obtain two kinds of carbon fibers impregnated with resin, and the temperature of the flat vulcanizer is adjusted to 90°C by a temperature control system. In the process of heating the pressing plate to a specified temperature, the mold of the carbon fiber impregnated with resin is placed in a flat vulcanizer for preheating. When the temperature of the pressing plate reaches the specified temperature, the pressure is adjusted to 5MPa by a pressure control system, and the molding system is started, and maintained at 90°C and 5MPa for 1h. Then adjust the temperature to 120°C, the pressure to 10MPa, and maintain for 2h. Finally, adjust the temperature to 150°C, the pressure is still 10MPa, and maintain for 3h. After the molding is completed, the heating system is turned off, and the mixture is naturally cooled to room temperature under the pressure-maintaining state, and then demolded to obtain a composite material sample strip.

[0042] The interlaminar shear strength and flexural strength of the desizing carbon fiber reinforced epoxy resin composite material of this embodiment are 50.9MPa and 808.42MPa respectively, and the interlaminar shear strength and flexural strength of the MPN and CNTs coated carbon fiber reinforced epoxy resin composite material are 74.25MPa and 1211.82MPa respectively. The carbon fiber treated with MPN and CNTs, with the increase of the number of oxygen-containing groups on the surface, the chemical bonding between the carbon fiber and the resin is tighter, the interface performance of the composite material is improved, and the interlaminar shear strength and flexural strength are increased.

[0043] Example 2

[0044] The carbon fiber was placed in a Soxhlet extractor, acetone was added, the temperature was raised to 68°C, and the reaction was carried out for 48 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0045] 4.25 g of tannic acid and 2.03 g of FeCl3·6H2O powder were dissolved in 200 ml of deionized water and stirred with a magnetic stirrer for 10 min (stirring and mixing at a rate of 1000 r / min) to obtain TA and Fe 3+ Metal polyphenol network (MPN) solution with a molar ratio of 1:3;

[0046] 0.1 g of carbon nanotubes was dissolved in 200 ml of deionized water and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension;

[0047] 10g of desized carbon fiber was first placed in an MPN solution for ultrasonic immersion for 10 minutes (the frequency of ultrasonic oscillation was 100kHz), then rinsed with deionized water for 3 times, and then the desized carbon fiber was placed in a CNTs suspension for ultrasonic immersion for 10 minutes (the frequency of ultrasonic oscillation was 100kHz), and rinsed with deionized water again for 3 times; it was placed in the above MPN solution for ultrasonic immersion for 10 minutes, taken out and rinsed with deionized water 3 times, and then placed in a CNTs suspension for ultrasonic immersion for 10 minutes, taken out and rinsed with deionized water until the supernatant was colorless and transparent, and then the carbon fiber was placed in an electric heated air drying oven and dried at 60°C for 6 hours to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

[0048] The scanning electron microscope image of the fracture surface of the desizing carbon fiber reinforced composite material obtained in Example 2 is as follows: Figure 2 As shown; Figure 3 This is a scanning electron microscope image of the fracture surface of the metal polyphenol network and carbon nanotube-coated carbon fiber reinforced composite material obtained in Example 2.

[0049] The desizing carbon fiber and MPN and CNTs coated carbon fiber obtained in Example 2 were respectively compounded with epoxy resin E51, and a composite material was prepared by a flat vulcanizer through a molding process (the desizing carbon fiber, metal polyphenol network and carbon nanotube coated carbon fiber were 63% of the composite material volume fraction), and the interlaminar shear strength (ILSS) and bending strength of the composite material were tested. The method for preparing the composite material is: the desizing carbon fiber and the metal polyphenol network and the carbon nanotube coated carbon fiber are fully impregnated in epoxy resin E51, respectively, to obtain two kinds of carbon fibers impregnated with resin, and the temperature of the flat vulcanizer is adjusted to 90°C by the temperature control system. In the process of heating the pressing plate to the specified temperature, the mold of the carbon fiber impregnated with resin is placed in the flat vulcanizer for preheating. When the temperature of the pressing plate reaches the specified temperature, the pressure is adjusted to 5MPa by the pressure control system, and the molding system is started, and it is maintained at 90°C and 5MPa for 1h. Then the temperature is adjusted to 120°C and the pressure is 10MPa, and it is maintained for 2h. Finally, the temperature is adjusted to 150°C, and the pressure is still 10MPa, and it is maintained for 3h. After the molding is completed, the heating system is turned off, and the mixture is naturally cooled to room temperature under the pressure-maintaining state, and then demolded to obtain a composite material sample strip.

[0050] The interlaminar shear strength and flexural strength of the MPN and CNTs coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 72.7 MPa and 929.57 MPa, respectively.

[0051] Example 3

[0052] The carbon fiber was placed in a Soxhlet extractor, acetone was added, the temperature was raised to 68°C, and the reaction was carried out for 48 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0053] 4.25 g of tannic acid and 2.03 g of FeCl3·6H2O powder were dissolved in 200 ml of deionized water and stirred with a magnetic stirrer for 10 min (stirring and mixing at a rate of 1000 r / min) to obtain TA and Fe 3+ Metal polyphenol network (MPN) solution with a molar ratio of 1:3;

[0054] 0.1 g of carbon nanotubes was dissolved in 200 ml of deionized water and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension;

[0055] The MPN solution and CNTs suspension were mixed and sonicated for 30 min;

[0056] 10 g of desized carbon fiber was placed in a mixed solution of MPN and CNTs and ultrasonically immersed for 10 min (the frequency of ultrasonic oscillation was 100 kHz), then rinsed with deionized water for 3 times, and rinsed with deionized water after taking out until the supernatant was colorless and transparent. The carbon fiber was then placed in an electric heated air drying oven and dried at 60°C for 6 h to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

[0057] The interlaminar shear strength and flexural strength of the MPN and CNTs coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 70.31 MPa and 1087.61 MPa, respectively.

[0058] It can be seen from Examples 1-3 that the different numbers of assembled layers and methods of the metal polyphenol network and carbon nanotubes will greatly change the structure and morphology of the carbon fiber surface, affecting its performance (interlaminar shear strength and bending strength).

[0059] Example 4

[0060] The carbon fiber was placed in a Soxhlet extractor, acetone was added, the temperature was raised to 68°C, and the reaction was carried out for 48 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0061] 4.25 g of tannic acid and 2.03 g of FeCl3·6H2O powder were dissolved in 200 ml of deionized water and stirred with a magnetic stirrer for 10 min (stirring and mixing at a rate of 1000 r / min) to obtain TA and Fe 3+ Metal polyphenol network (MPN) solution with a molar ratio of 1:3;

[0062] 10 g of desized carbon fiber was first placed in the MPN solution for ultrasonic immersion for 10 min (the frequency of ultrasonic oscillation was 100 kHz), then rinsed with deionized water three times until the supernatant was colorless and transparent, and then the carbon fiber was placed in an electric heated air drying oven and dried at 60°C for 6 h to obtain metal polyphenol network-coated carbon fiber.

[0063] The MPN coated carbon fiber obtained in Example 4 was compounded with epoxy resin E51, and a composite material (the MPN coated carbon fiber accounted for 63% of the volume fraction of the composite material) was prepared by a flat vulcanizer through a molding process, and the interlaminar shear strength (ILSS) and bending strength of the composite material were tested. The specific process was the same as in Example 1.

[0064] The interlaminar shear strength and flexural strength of the MPN-coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 61.23 MPa and 927.59 MPa, respectively.

[0065] Example 5

[0066] The carbon fiber was placed in a Soxhlet extractor, acetone was added, the temperature was raised to 68°C, and the reaction was carried out for 48 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0067] 0.1 g of carbon nanotubes was dissolved in 200 ml of deionized water and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension;

[0068] 10 g of desized carbon fiber was placed in a CNTs suspension and ultrasonically immersed for 10 min (the frequency of ultrasonic oscillation was 100 kHz), and then rinsed with deionized water for 3 times until the supernatant was colorless and transparent. The carbon fiber was then placed in an electric heated air drying oven and dried at 60°C for 6 h to obtain carbon nanotube-coated carbon fiber.

[0069] The CNTs-coated carbon fiber obtained in Example 5 was compounded with epoxy resin E51, and a composite material (the CNTs-coated carbon fiber was 63% of the volume fraction of the composite material) was prepared by a flat vulcanizer through a molding process, and the interlaminar shear strength (ILSS) and bending strength of the composite material were tested. The specific process is the same as in Example 1.

[0070] The interlaminar shear strength and flexural strength of the CNTs-coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 63.55 MPa and 895.49 MPa, respectively.

[0071] It can be seen from Examples 1, 4, and 5 that the performance of the simple MPN-coated carbon fiber reinforced epoxy resin-based composites and the CNTs-coated carbon fiber reinforced epoxy resin-based composites are improved compared with the desizing carbon fiber reinforced epoxy resin-based composites, but are lower than the MPN and CNTs-coated carbon fiber reinforced epoxy resin-based composites.

[0072] Example 6

[0073] The difference from Example 1 is that 0.05 g of carbon nanotubes are dissolved in 200 ml of deionized water, and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension, and the rest is the same.

[0074] Example 7

[0075] The difference from Example 1 is that 0.15 g of carbon nanotubes are dissolved in 200 ml of deionized water, and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension, and the rest is the same.

[0076] Example 8

[0077] The difference from Example 1 is that 0.25 g of carbon nanotubes are dissolved in 200 ml of deionized water, and ultrasonicated at 100 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension, and the rest is the same.

[0078] By comparison, it is found that the interlaminar shear strength and bending strength of Examples 6 and 7 are improved compared with the simple desizing carbon fiber reinforced epoxy resin-based composite material, but are lower than Example 1. At the same time, the performance of Example 8 is lower than that of Examples 6 and 7.

[0079] Tannic acid can provide active functional groups to promote the dispersion and uniform attachment of CNTs on the surface of carbon fibers. The modification of tannic acid can improve the surface wettability of carbon fibers, thereby helping CNTs to attach better. In this way, the combination of the two helps to form a more stable and uniform composite structure. Tannic acid can be used as a surface modifier to increase the hydrophilicity of carbon fibers and promote the uniform dispersion of CNTs. At the same time, the introduction of CNTs can increase the mechanical strength and conductivity of the composite material, compensating for the strength reduction that may be caused by tannic acid.

[0080] Example 9

[0081] The carbon fiber was placed in a Soxhlet extractor, acetone was poured in, the temperature was raised to 60°C, and the reaction was carried out for 36 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0082] 4.25 g of tannic acid and 0.677 g of FeCl3·6H2O powder were dissolved in 200 ml of deionized water and stirred with a magnetic stirrer for 5 min (stirring and mixing at a rate of 900 r / min) to obtain TA and Fe 3+ Metal polyphenol network (MPN) solution with a molar ratio of 1:1;

[0083] 0.1 g of carbon nanotubes was dissolved in 200 ml of deionized water and ultrasonicated at 80 kHz for 5 min to obtain a carbon nanotube (CNTs) suspension;

[0084] 10g of desized carbon fiber was first placed in an MPN solution for ultrasonic immersion for 5 minutes (the frequency of ultrasonic oscillation was 80kHz), then rinsed with deionized water for 3 times, and then the desized carbon fiber was placed in a CNTs suspension for ultrasonic immersion for 5 minutes (the frequency of ultrasonic oscillation was 80kHz), and then rinsed with deionized water for 3 times until the supernatant was colorless and transparent, and then the carbon fiber was placed in an electric heated air drying oven and dried at 50°C for 5 hours to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

[0085] The interlaminar shear strength and flexural strength of the MPN and CNTs coated carbon fiber reinforced epoxy resin based composite materials obtained in this example are 71.99 MPa and 1190.23 MPa, respectively.

[0086] Example 10

[0087] The carbon fiber was placed in a Soxhlet extractor, acetone was poured in, the temperature was raised to 80°C, and the reaction was carried out for 72 hours to remove the sizing agent on the surface of the carbon fiber. After the reaction was completed, the carbon fiber was taken out, washed with deionized water for 5 times, and dried to obtain the desized carbon fiber.

[0088] 4.25 g of tannic acid and 1.35 g of FeCl3·6H2O powder were dissolved in 200 ml of deionized water and stirred with a magnetic stirrer for 15 min (stirring and mixing at a rate of 1200 r / min) to obtain TA and Fe 3+ Metal polyphenol network (MPN) solution with a molar ratio of 1:2;

[0089] 0.1 g of carbon nanotubes was dissolved in 200 ml of deionized water and ultrasonicated at 120 kHz for 30 min to obtain a carbon nanotube (CNTs) suspension;

[0090] 10 g of desized carbon fiber was first placed in an MPN solution for ultrasonic immersion for 20 min (the frequency of ultrasonic oscillation was 120 kHz), then rinsed with deionized water for 3 times, and then the desized carbon fiber was placed in a CNTs suspension for ultrasonic immersion for 20 min (the frequency of ultrasonic oscillation was 120 kHz), and then rinsed with deionized water for 3 times until the supernatant was colorless and transparent, and then the carbon fiber was placed in an electric blast drying oven and dried at 70°C for 7 h to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

[0091] The interlaminar shear strength and flexural strength of the MPN and CNTs coated carbon fiber reinforced epoxy resin based composite materials obtained in this example are 72.28 MPa and 1179.79 MPa, respectively.

[0092] The raw materials listed in the present invention, as well as the upper and lower limits and interval values ​​of the raw materials in the present invention, and the upper and lower limits and interval values ​​of the process parameters can all realize the present invention, and the embodiments are not listed one by one here.

[0093] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A method for preparing an organic-inorganic hybrid structure using the surface of carbon fiber, characterized in that: The preparation method comprises the following steps: Step 1: desizing the carbon fiber in acetone to obtain desizing carbon fiber; Step 2: dissolving tannic acid and FeCl3·6H2O in deionized water, stirring and mixing to obtain a metal polyphenol network solution, i.e., an MPN solution; wherein the molar ratio of tannic acid to FeCl3·6H2O is 1:1-3; Step 3: dissolving carbon nanotubes in deionized water and ultrasonically obtaining a carbon nanotube suspension, i.e., a CNTs suspension; Step 4: firstly place the desized carbon fiber in the MPN solution for ultrasonic immersion, then place the MPN-coated carbon fiber in the CNTs suspension for ultrasonic immersion after rinsing, then rinse again, repeat the above operation until the supernatant is colorless and transparent, and then dry to obtain the metal polyphenol network and carbon nanotube-coated carbon fiber; The mass ratio of tannic acid to carbon nanotubes is 4.25:0.05-0.

15.

2. The method for preparing an organic-inorganic hybrid structure using the carbon fiber surface according to claim 1, characterized in that: In the step 1, the acetone desizing temperature is 60° C. to 80° C., and the desizing time is 36 to 72 hours.

3. The method for preparing an organic-inorganic hybrid structure using the carbon fiber surface according to claim 1, characterized in that: In the step 2, the mass volume ratio (g:ml) of tannic acid and deionized water is 4.25:200; the mixture is stirred and mixed with a magnetic stirrer for 5-15 minutes at a stirring rate of 900-1200 r / min; the tannic acid and Fe in the obtained MPN solution are 3+ The molar ratio is 1:1~3.

4. The method for preparing an organic-inorganic hybrid structure using the carbon fiber surface according to claim 1, characterized in that: In step 3, the ultrasonic frequency is 80 to 120 kHz, and the ultrasonic time is 5 to 30 minutes.

5. The method for preparing an organic-inorganic hybrid structure using the carbon fiber surface according to claim 1, characterized in that: In step 4, the ultrasonic frequency is 80-120 kHz; the ultrasonic immersion is 5-20 min min, the drying temperature is 50-70° C.; the drying time is 5-7 h; and the immersion cycle number is 1-3 times.

6. The method for preparing an organic-inorganic hybrid structure using the carbon fiber surface according to claim 1, characterized in that: The mass ratio of the MPN solution to the CNTs suspension in step 4 is 1-2:1-2; the mass ratio of the desized carbon fiber to the tannic acid in step 2 is 10:4.

25.

7. The method for preparing an organic-inorganic hybrid structure using the carbon fiber surface according to claim 1, characterized in that: The following steps are involved: Step 1: Put the carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48 hours, take it out after the reaction is completed, wash it with deionized water, and dry it to obtain desized carbon fiber; Step 2: Dissolve 4.25 g tannic acid and 2.03 g FeCl3·6H2O powder in 200 ml deionized water and stir with a magnetic stirrer for 10 min at a stirring rate of 1000 r / min to obtain TA and Fe 3+ Metal polyphenol network solution with a molar ratio of 1:3; Step 3: Dissolve 0.1 g of carbon nanotubes in 200 ml of deionized water and ultrasonicate at 100 kHz for 30 min to obtain a carbon nanotube suspension; Step 4: Place 10g of desized carbon fiber in the MPN solution for ultrasonic immersion for 10 minutes, then rinse with deionized water for 3 times, then place the MPN-coated carbon fiber in the CNTs suspension for ultrasonic immersion for 10 minutes, rinse with deionized water again for 3 times until the supernatant is colorless and transparent, and then place it in a drying oven at 60°C for 6 hours to obtain a metal polyphenol network and carbon nanotube-coated carbon fiber.

8. The metal polyphenol network and carbon nanotube-coated carbon fiber obtained according to any one of the preparation methods of claims 1-7.

9. The use of the metal polyphenol network and carbon nanotube coated carbon fiber in a composite material according to claim 8, characterized in that: The metal polyphenol network and the carbon nanotube-coated carbon fiber are compounded with epoxy resin and a composite material is prepared through a molding process.

10. The use of the metal polyphenol network and carbon nanotube coated carbon fiber in a composite material according to claim 9, characterized in that: The metal polyphenol network and the carbon nanotube coated carbon fiber account for 63% of the volume fraction of the composite material; the metal polyphenol network and the carbon nanotube coated carbon fiber are fully impregnated in epoxy resin E51, the temperature of the vulcanizer is adjusted to 90°C, and the mold wrapped with the metal polyphenol network and the carbon nanotube coated carbon fiber impregnated with the resin is placed in the vulcanizer for preheating, and then the pressure is adjusted to 5MPa through the pressure control system, and the molding system is started and maintained at 90°C and 5MPa for 1h; then the temperature is adjusted to 120°C and the pressure is 10MPa, and maintained for 2h; finally, the temperature is adjusted to 150°C and the pressure is 10MPa, and maintained for 3h; after the molding is completed, it is naturally cooled to room temperature under the pressure holding state, and demolded to obtain a composite material.

Citation Information

Patent Citations

  • Method for loading carbon fiber surface with carbon nanotubes

    CN106149357A

  • Preparation method of super-hydrophobic flame-retardation material

    CN108396552A

  • Preparation method of carbon nanotube-carbon fiber mixed enhanced epoxy resin composite material

    CN108976711A

  • Fiber surface modification method

    CN116479651A

  • Fibrous composite material and preparation method therefor

    WO2024108621A1